Cochrane Database of Systematic Reviews 2011
DOI: 10.1002/14651858.cd009154.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Luteal phase support for assisted reproduction cycles

Abstract: This review showed a significant effect in favour of progesterone for luteal phase support, favouring synthetic progesterone over micronized progesterone. Overall, the addition of other substances such as estrogen or hCG did not seem to improve outcomes. We also found no evidence favouring a specific route or duration of administration of progesterone. We found that hCG, or hCG plus progesterone, was associated with a higher risk of OHSS. The use of hCG should therefore be avoided. There were significant resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
81
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 130 publications
2
81
0
5
Order By: Relevance
“…Гормональный профиль лютеиновой фазы цикла стимуляции суперовуляции препаратами гонадотро-пинов отличается от такового в лютеиновую фазу естественного цикла более высокой концентрацией прогестерона и эстрадиола, укорочением периода плато и выраженным снижением на 7-10-й день после введения триггера овуляции [14]. Считается, что стимуляция яичников приводит к образованию множества лютеиновых кист, неспособных обеспе-чить адекватную продукцию прогестерона.…”
Section: влияние уровня эстрадиола на исход экоunclassified
See 1 more Smart Citation
“…Гормональный профиль лютеиновой фазы цикла стимуляции суперовуляции препаратами гонадотро-пинов отличается от такового в лютеиновую фазу естественного цикла более высокой концентрацией прогестерона и эстрадиола, укорочением периода плато и выраженным снижением на 7-10-й день после введения триггера овуляции [14]. Считается, что стимуляция яичников приводит к образованию множества лютеиновых кист, неспособных обеспе-чить адекватную продукцию прогестерона.…”
Section: влияние уровня эстрадиола на исход экоunclassified
“…По данным 7 исследований, частота наступления кли-нической беременности не различалась при допол-нительном назначении препаратов эстрадиола. Од-нако анализ подгрупп с разным способом введения препаратов выявил повышение частоты наступления клинической беременности в подгруппе женщин, принимавших прогестерон + трансдермальный эстрадиол по сравнению с женщинами, принимав-шими только прогестерон (OR 0,50, 95% CI 0,31-0,82) [14].…”
Section: влияние уровня эстрадиола на исход экоunclassified
“…Luteal phase support improves implantation rate and thus pregnancy rates, but the ideal method is still unclear. A large recent Cochrane review showed a significant effect in favor of progesterone for luteal phase support, favoring synthetic progesterone over micronized progesterone [1]. Overall, the addition of other substances such as estrogen or hCG did not seem to improve outcomes.…”
Section: Introductionmentioning
confidence: 96%
“…They found that hCG, or hCG plus progesterone, was associated with a higher risk of ovarian hyperstimulation syndrome (OHSS). The use of hCG should therefore be avoided [1]. There were significant results showing beneficial effects from the addition of GnRH agonist to progesterone in terms of the outcomes of live birth, clinical pregnancy, and ongoing pregnancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation